Оценка погрешности эталонной кондуктометрической ячейки, обусловленной неэквипотенциальностью поверхности электродов - Глухенький, А.И.; Михаль, А.А. (Технічна електродинаміка, 2011)
The mathematical model for error estimation of the conversion of standard four-electrode conductometric cell conditional on non-equipotentiality of electrode face has been worked out. The conditions under which this error does not exceed 10 ppm have been specified.